New Approaches in Oncology for Repositioning Drugs: The Case of PDE5 Inhibitor Sildenafil - Cruz-Burgos, Marian; Losada-Garcia, Alberto; Cruz-Hernández, Carlos D.; Cortés-Ramírez, Sergio A.; Camacho-Arroyo, Ignacio; Gonzalez-Covarrubias, Vanessa; Morales-Pacheco, Miguel; Trujillo-Bornios, Samantha I.; Rodríguez-Dorantes, Mauricio (Frontiers in Oncology, 2021)
Recently, the use of already-approved drugs for new or alternative treatments has been a beneficial, although challenging endeavor in medicine. New drug applications approvals by the FDA are registered to target specific diseases, offering a contribution to treat specific pathologies for a particular group of patients. Nevertheless, most drugs have intricate mechanisms of action and hence, their effects are not usually restricted to one organ or one disease. Diverging from its original intent offers an opportunity to repurpose previously known and approved drugs to treat other ailments. This is the case of sildenafil (Viagra), an inhibitor of phosphodiesterase-5 (PDE5), a potent vasodilator originally designed to treat systemic hypertension and angina, currently commercialized for the treatment of erectile dysfunction. sildenafil, tadalafil, and vardenafil are PDE5 inhibitors that prolong the physiological effects of nitric oxide and cGMP signaling. The wide range of effects of this inhibition on the vasculature has not been comprehensively dissected, but it offers a large therapeutic potential for several diseases. In addition, some of PDE5 inhibitors effects seem to involve many cell pathways related with kidney disease, diabetes mellitus, and cancer development. In this review, we discuss the effects of PDE5 inhibitors and their therapeutic repurposing in different types of cancer.